Analisis Dampak Starategi Pemasaran Media Sosial terhadap Pertumbuhan Ekonomi - Gladis Gresya Soares; Reynaldino Ritwanto Tabang Jun; Maria Nelldyandra Puspita; Yohanes Pemandi Lian (AKUNTANSI 45, 2026)
This study aims to see how the use of social media can affect economic development and growth in MSME actors. Data was collected through interviews with three MSMEs, namely Balado Chips "Mak Sari" MSMEs, Cake Shop MSMEs, and MSMEs for basic food stalls. The results of the study show that MSMEs that have utilized social media such as WhatsApp, Facebook, and Instagram are able to increase sales and attract more customers, even one of the MSMEs experienced an increase in sales of up to 30% after actively promoting on social media. Meanwhile, MSMEs that have not used social media still have limited marketing reach and have difficulty introducing products to the wider community. These findings also show that there are still business actors who need assistance in the use of technology due to the limitations of digital knowledge. In addition, consistency in creating attractive promotional content and the ability to respond quickly to customers are also factors that support the success of digital marketing. Overall, the study concludes that social media has an important role in helping MSMEs grow, increase business competitiveness, expand marketing networks, and contribute to local economic growth, especially if used with the right and sustainable marketing strategy.